The Use of Information Technology in Course Delivery and Students’ Cheating: Case Study - UZIAK, JACEK; LORENCOWICZ, EDMUND; KOSZEL, MILAN; KOCIRA, SŁAWOMIR (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2018)
Information Technology (IT) entered the world of education with authority and with general assumption that it would enhance students’ learning. It is used in the educational environment for many uses, with class delivery as one of the most important purposes. The aim of the study was to investigate the preferences in the delivery methods by students and compare with those favoured by the instructors. Additionally, the study assessed the use of IT in preparation (by instructors) and access (by students) of material related to learning. A separate issue addressed was classroom cheating by students and IT application for that purpose. The study indicated a clear preference by both students and instructors for blended learning of traditional face to face lecturing with additional on-line material. The study also confirmed the use of IT as a tool for class cheating. Although reluctantly, up to 73% of students confessed to cheating using one or other method.